P55 Triage by methylation marker analysis versus colposcopy biopsy in women who test HPV-positive or abnormal LBC results on cervical samples to triage cervical cancer and HSIL for further treatment. (1st November 2019) - Gu, Y; Zhou, G; Ding, J; Hua, K
Abstract : Introduction/Background: While colposcopy screening was successful in screening cervical cance, it has limitations like subjectivity, interobserver variability, modest sensitivity. The study aims to evaluate the efficacy of colposcopy and CareMe Pluse methylation for triage cervical cancer and HSIL for future treatment. Methodology: In the prospective observational multi-center study, 4070 patients with HPV-positive or abnormal LBC results underwent colposcopy-examination to identify the grade of cervical lesion, meanwhile the cervical scrapes were tested for DNA methylations. 607 women diagnosed as ≥HSIL via colposcopy-biopsy and then underwent LEEP (Loop Eelectrosurgical Excision Procedure). Depending on the pathology after LEEP as golden standard, the predictive performance of methylation analysis and colposcopy-biopsy were compared. The sensitivity and specificity of several other methylation tests were analyzed to determine the optimal methylation strategy. Results: The predictive performance of CareMe-plus methylation was evaluated by comparing the sensitivity and specificity of methylation tests and colposcopy biopsy in patients who underwent LEEP (n=607). Depending on the pathology after LEEP as golden standard, the predictive performance of CareMe-plus methylation was significantly greater than colposcopy-biopsy for cervical cancer, CareMe-plus methylation analysis revealed a significant discrimination of women with cervical cancer from those with ≤HSIL (P=0.022). ROC curve analysis showed an AUC of 0.869. The predictive performance of CareMe-plus methylation was significantly greater than colposcopy-biopsy for HSIL+, CareMe-plus methylation analysis revealed a significant discrimination of women with HSIL+ from those with ≤LSIL (P=0.026). The CareMe-plus methylation analysis was superior to other alternative methylations to triage patients for further treatment. When compared the predictive performance of several methylation tests for cervical cancer, CareMe and CareMe-plus is greater than EPB41L3 and QIsure. Conclusion: CareMe-plus methylation assay may be applicable to identify HPV-positive or abnormal LBC women with a high-risk of high grade lesion or cervical cancer. It may triage patients for accurate further treatment when combining with colposcopy biopsy. Disclosure: Nothing to disclose.